2018
DOI: 10.1071/cp17284
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic diversity among chickpea (Cicer arietinum) genotypes as a function of drought tolerance

Abstract: Diversity as a function of drought tolerance may be identified by morphological characters, and molecular tools used to find the most divergent genotypes for breeding programs for drought tolerance in future. The narrow genetic base of chickpea can be circumvented by using diverse lines in breeding programs. Forty chickpea genotypes were studied for their morphological and molecular diversity with an objective of identifying the most diverse drought-tolerant lines. In total, 90 alleles were detected with 3.6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…Similar to our results the average PIC values of 0.77, 0.75, 0.75, 0.72, were observed by [13,29,35,43], respectively. Comparatively, a high average PIC value of 0.854 has been reported by [30], and [17,36,[44][45] revealed an average PIC value of 0.53, 0.60, 0.68, and 0.43, respectively which is relatively less than that of the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…Similar to our results the average PIC values of 0.77, 0.75, 0.75, 0.72, were observed by [13,29,35,43], respectively. Comparatively, a high average PIC value of 0.854 has been reported by [30], and [17,36,[44][45] revealed an average PIC value of 0.53, 0.60, 0.68, and 0.43, respectively which is relatively less than that of the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…In the present study, the pooled ANOVA for all measured traits, including root-related traits, showed highly significant differences between genotypes under irrigated and rainfed conditions at both locations. Combined ANOVA in several studies also showed significant differences for various morphological and physiological traits (Hamwieh et al, 2013;Pang et al, 2017;Purushothaman et al, 2017;Sachdeva et al, 2018) and for root-related traits (Varshney et al, 2014;Purushothaman et al, 2017). Significant differences were also observed for genotype × environment (G × E) interactions for almost all the measured traits including root-related traits.…”
Section: Discussionmentioning
confidence: 88%
“…Relatively lesser decrease in MSI was observed in BGD72 (7.69%), ICCV10 (9.09%) and ICCV3311 (12%) with higher RWC (%) signifying their tolerance to drought. RWC and MSI have been suggested for screening the germplasm for drought tolerance [2]. Drought stress also hinders photosynthetic machinery of plants by bringing about changes in the chlorophyll content [47].…”
Section: Plos Onementioning
confidence: 99%
“…Chickpea (Cicer arietinum L.), one of the earliest food legume crop with a diploid chromosome number of 16 is cultivated in the tropics all over the world [1] and belongs to the family Fabaceae [2]. India being the largest producer of chickpea produces 68% of the total world production and about 9.21Mha area is under chickpea cultivation producing 8.88Mt [3].…”
Section: Introductionmentioning
confidence: 99%